1998
DOI: 10.1902/jop.1998.69.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Investigation of Gingival Tissue From Patients With Rapidly Progressive Periodontitis

Abstract: In this study, fine structural features of the pocket walls in rapidly progressive periodontitis (RPP) and adult periodontitis (AP) in 20 cases were compared using light and transmission electron microscopy. Gingiva was also obtained from a control group of periodontally healthy teeth. Clinical parameters were assessed in both RPP and AP patients and in controls. Bone destruction and attachment loss were more marked in RPP than in AP. Light microscopical observations of inflamed RPP tissue as compared to AP sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…P. gingivalis, a key putative periodontal pathogen, can invade the gingival tissue in advanced periodontitis (19,39) and invade cultured epithelial cells in vitro (25,41). P. gingivalis also produces enzymes that degrade a broad spectrum of host proteins, including epithelial adhesion molecules (22,48) and extracellular matrix proteins (44).…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis, a key putative periodontal pathogen, can invade the gingival tissue in advanced periodontitis (19,39) and invade cultured epithelial cells in vitro (25,41). P. gingivalis also produces enzymes that degrade a broad spectrum of host proteins, including epithelial adhesion molecules (22,48) and extracellular matrix proteins (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that macrophages in the gingival epithelial surface beneath periodontal pockets engulf Porphyromonas gingivalis in situ [12]. P. gingivalis-induced phagocytic activity by murine macrophages has been found to be enhanced by interferon (IFN)-ª, but not IL-4 and IL-10 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The organism can invade gingival tissue in advanced periodontitis (18) and can be taken up by gingival and pocket epithelial cells, oral epithelial cell lines, and endothelial cells in vitro (13,23,33,40). The nature of the eukaryotic surface receptor molecules and the signal transduction pathways required for internalization of P. gingivalis by oral epithelial cells remain to be clarified.…”
mentioning
confidence: 99%